PENGARUH DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. BUKIT MAKMUR MANDIRI UTAMA JOB SITE BINSUA (BINUNGAN SUARAN) - Ganie, Djupiansyah; Abidin, Zainal (CAM JOURNAL, Jurnal Agen Perubahan Manajemen, 2017)
The aimed of this study is to analyze the influence of  discipline for working and work facilities toward employee productivity at PT. Bukit Makmur Mandiri Utama Job Site Binsua   Based on the results of the study can be concluded that the  work discipline partially have a significant effect on employee productivity at PT. Bukit Makmur Mandiri Utama Job Site Binsua, this is evidenced from the results of Test t that get the value of t-count> t table or 2.251> 1.985 with a significance value of 0.025 <0.05. Work facilities partially have a significant effect on employee productivity at PT. Bukit Makmur Mandiri Utama Job Site Binsua, this is evidenced from the results of Test t that obtained the value of t-count> t-table or 2.354> 1.985 with a significance value of 0.047 <0.05.  The discipline for working and work facilities integrated have a significant effect on employee productivity at PT. Bukit Makmur Mandiri Utama Job Site Binsua, evidenced from the result of Test F where the value of F-calculated (25.233)> of F-table value (3.09) with significance value 0.001 <0.05. Therefore,  the accepted the hypothesis that has been proposed, that the  discipline for working and work facilities have a significant effect on employee productivity at PT. Bukit Makmur Mandiri Main Job Site Binsua partially or simultaneously.